(untitled) (American Journal of Islam and Society, 2006)
In this issue, we move away from our customary focus on the Muslim Middle East and Muslims in the West and turn toward Southeast Asia and China. Here, we find Muslim communities that seem not to be so entranced by what we in the West consider to be the most pressing issues: the Muslim world vs. the West and/or modernity, the Abrahamic faiths trialogue, political and economic reform, the suitability of western-style democracy in Muslim countries, and the rise of Islamic “fundamentalism,” “terrorism,” “extremism,” or whatever similar term the media throws at us. Excluding Indonesia and Malaysia, the overriding concerns of these Muslims appear to be different, for they are often viewed as unwanted or ignored minority communities. For example, Muslims living in Xinjiang, southern Thailand, and the southern Philippines are confronted daily by hostile or indifferent regimes that want their natural resources and land. Thus, their main concerns are actual (as opposed to theoretical) justice, being allowed to remain “different” instead of being forced to assimilate, and passing on their religious and cultural identities in a hostile environment. In interfaith terms, their intellectuals are involved in other discourses: Islam and Buddhism, Confucianism, communism, folk religion, cultural chauvinism, and others. To cite an example, one of my Cham Muslim friends from Vietnam translated the Qur’an into Vietnamese several years ago. According to him, the hardest part was translating such monotheistic concepts as God, sin, final judgment, good, and evil into a non-monotheistic language that has no words for such concepts. One of our articles (Peterson) deals with how Chinese Muslim scholars of the pre-modern era tried to solve this problem. Several of our articles deal with China, whose rite of passage into modernity might have killed a lesser nation. Within the space of 100 years, it was ruled by a highly traditional empire engulfed in its own hubris, a nationalist republican regime beset by a virulent communist insurgency and Japanese invasion, and an extremely radical revolutionary communist regime. And now it is an economic dynamo, due to its “capitalism with Chinese characteristics.” But what do we know of its Muslims, other than that the Turkic Muslims of Xinjiang continue to be restive and that the Bush administration has accepted Beijing’s claim that several of Xinjiang’s secessionist groups have links with the Taliban and al-Qaeda? ...